A set of international OECD and ICGN Corporate Governance Standards after financial crisis, Corporate scandals and manipulation - applications for Nigeria and implications for developing countries - Ngoc, Huy Dinh Tran; Thi, Thuy Nguyen; Phuong, Le Thi My; Dat, Pham Minh; Dung, Vu Trung; Manh, Phan Tien (Zielona Góra: Faculty of Economics and Management Press)
A statement by ACCA in May 2009 that any corporate governance system should consider factors such as transparency, accountability, fairness and responsibility, raises issues in this field over past few years. There are also a few researches which have been done in the field of international corporate governance standards. This paper chooses a different analytical approach and among its aims is to give some certain systematic conclusions.
Keywords: corporate governance; board structure; code of best practice; financial crisis; corporate scandals; market manipulation; internal audit; ład korporacyjny; struktura zarządu; kodeks dobrych praktyk; kryzys finansowy; skandale korporacyjne; audyt wewnętrzny; manipulacje rynkowe